An Extended Macro-Finance Model with Financial Factors - Dewachter, Hans; Iania, Leonardo (Journal of Financial and Quantitative Analysis, 2011)
Abstract This paper extends the benchmark macro-finance (MF) model by introducing, next to the standard macroeconomic factors, additional liquidity-related and return-forecasting factors. Liquidity factors are obtained from a decomposition of the money market spread, while the return-forecasting (risk premium) factor is extracted by imposing a single-factor structure on the 1-period expected excess holding return. The model is estimated on U.S. data using Markov chain Monte Carlo techniques. Two findings stand out. First, the model significantly outperforms most structural and nonstructural MF yield curve models in terms of the cross-sectional fit of the yield curve. Second, financial shocks have a statistically and economically significant impact on the yield curve.